Enhanced pH stability, cell viability and reduced degradation rate of poly(L-lactide)-based composite in vitro: effect of modified magnesium oxide nanoparticles. Issue 5 (24th March 2017) - Yang, Jinjun; Cao, Xiuxiang; Zhao, Yun; Wang, Liang; Liu, Bei; Jia, Junping; Liang, Hui; Chen, Minfang
Abstract: The modified MgO nanoparticles (m-MgO-NPs) by a copolymer containing the malic acid and low molecular weight poly(L-lactide) (poly(L-lactide- co -malic acid), PLMA) have been successfully prepared. MgO nanoparticles (MgO-NPs) were coated by the PLMA and m-MgO-NPs were uniformly dispersed in the PLLA matrix to a novel biocomposite material (PLLA/m-MgO-NPs) with more excellent interface bonding and uniformer dispersion, compared to the PLLA/MgO-NPs. Compared to neat PLLA and PLLA/MgO-NPs film, the m-MgO-NPs not only shown the obvious neutralization effect on the acidic solution in the degradation of the PLLA and better hydrophilicity, but also exhibited the higher cell viability and decrease the toxicity to the cell in the degradation process of PLLA in vitro . In addition, m-MgO-NPs also reduced the degradation rate of the PLLA. The mechanisms for the excellent dispersion of nanoparticles, enhanced pH stability, reduced degradation rate of the PLLA and the cell viability in vitro in the case of PLLA/m-MgO-NPs have also been proposed and discussed in detail. Abstract :